A FIELD RESEARCH ON HOW STUDENTS PERCEIVE THE DIGITAL BUSINESS OFFERED BY CURRENT COMMUNICATION TECHNOLOGIES (Third Sector Social Economic Review, 2022)
Many virtual revolutions of industry 4.0 such as artificial intelligence, virtual reality, remote control are taking place. Especially with the pandemic process, the intensive use of distance education technologies in education has caused almost all of the society to operate and produce on the ground of a digital public space. This driving force has resulted in young people thinking more effectively about business models on digital platforms. The pandemic has accelerated this process, forcing traditional business areas to go digital. This article claims to be original by trying to understand how students perceive digital job opportunities in cities other than big cities such as Istanbul, Ankara and Izmir. Considering how the situation is progressing in other provinces with relatively limited access to digital technologies, the situation in Anatolia gains importance. For this reason, it has been tried to understand how students who study at two different universities in Anatolia (Bolu and Aydın) interpret today's digital business opportunities by using the technique of in-depth interviews, and in which areas they operate and create an intense demand. Considering all the answers, it has been determined that the participants in the universities where the subject of digital entrepreneurship is examined differently from the big/metropolitan cities such as Istanbul, Izmir and Ankara are in a very basic level of development.
Keywords: Digital Business; Digital Economy; Intercultural Communication; Distance Education; Pandemic